2021
DOI: 10.1080/13639080.2021.1931666
|View full text |Cite
|
Sign up to set email alerts
|

Career readiness: developing graduate employability capitals in aspiring media workers

Abstract: Teaching students aspiring to media work presents the educator with a fundamental dilemma. On the one hand, students require the knowledge and skills necessary to find and sustain employment within existing industry practices, systems and structures. On the other hand, students need to be prepared for the uncertain and shifting nature of media work, and highly problematic aspects of some of those selfsame practices, systems and structures. How do you ensure the former without condoning or under-playing the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…According to Wallis (2021), aspiring media workers need to be prepared for the changing nature of media work, therefore they need the skills to adapt to a career over time and be a flexible workforce. Higher education needs to prepare students for the established industry practices and the shifting and evolving nature of media employment.…”
Section: Background Active Learning In He and Pedagogical Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wallis (2021), aspiring media workers need to be prepared for the changing nature of media work, therefore they need the skills to adapt to a career over time and be a flexible workforce. Higher education needs to prepare students for the established industry practices and the shifting and evolving nature of media employment.…”
Section: Background Active Learning In He and Pedagogical Activationmentioning
confidence: 99%
“…Higher education needs to prepare students for the established industry practices and the shifting and evolving nature of media employment. For such, education needs to improve "graduate capital" (human capital; social capital; cultural capital; psychological capital and identity capital) (Wallis, 2021). This means that students need skills, they need to interact with others, have networking abilities, understand the cultural aspects of the work environment and position themselves in the job market to have "career readiness" (Wallis, 2021).…”
Section: Background Active Learning In He and Pedagogical Activationmentioning
confidence: 99%
“…In some cases, students are not aware of the skills required by the labour market (Dolce et al 2020;Lockett and Feng 2019;Amoroso and Burke 2018). As a result, students tend to both inflate and underestimate their employability skills (Gawrycka et al 2020;Wallis 2021). A study on Vietnam found that employers were not satisfied with graduates' employability assets during recruitment, and graduating students had poor understanding of the real needs of the labour market (T. T. Tran 2017).…”
Section: Students' Responsibilitymentioning
confidence: 99%
“…Unlike all the other skills studied in this paper, the difference in scores across the nine different types of academic skills was not significant (F = 0.559, p = 0.812), suggesting that students probably gave themselves high scores across any indicators classified as 'academic skills'. Several studies have found that students do overestimate their academic capabilities and competencies (Wallis 2021;McArthur et al 2017;Koys et al 2019).…”
Section: Academic Skillsmentioning
confidence: 99%
“…Previous research on employability has acknowledged the importance of holistic approaches to this topic, specifically approaches that take into account a combination of resources beyond a skill-centric focus (Cole & Donald, 2022 ), including factors such as personal characteristics, academic achievements and graduate skills (Byrne, 2022 ). Among various such approaches, a focus on capital — such as human capital (Schultz, 1961 ) — has been widely adopted to understand the resources that are necessary to promote graduates’ career readiness (Wallis, 2021 ). Human capital theory implies that education is a form of individual investment aimed at obtaining explicit returns regarding the individual’s career path, with the purpose of ensuring that individuals, by investing in their education, develop their human capital to increase their competitiveness in the labour market (Cai, 2013 ; Nimmi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%